Experience of recreating children stories from folklore: criteria analysis - Hosseini, Sayyid (Humanities Journal of University of Zakho, 2022)
Children literature is an important and fundamental for transforming culture, literary text, education and leasure in every nation. In developed countries researchers and practitioners are working on children literature theoretically and practically. In other words this field is scientifically under investigation and is used practically. Unfortunately, there is few resources to guide Kurdish writers for rewriting and recreating children stories from folklore, while Kurdish folks and culture has the potential to create all genres of children literatures. In this research we reviewed related literature to compile basics of recreation and exemplify those principles as guideline with comparing "Danke Henare" text with compiled basics. As a result, researchers and practitioners may use this work as sample in recreating children stories from folks.